The Function of Digital Public Relations in Improving the Image of PT. Jakarta Transportasi - Tamara Silvia Natasya; Geofakta Razali (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the era of globalization, the role of Public Relations is very important for an agency or company. Improving and promoting the company's image is also in the hands of Public Relations, so a Public Relations person must be able to interact well with others and understand the company's side. The purpose of this study is to find out and analyze how Public Relations functions in improving the image of PT. Jakarta transportation as a public transportation mode company. In addition, this study aims to determine and analyze the obstacles of Public Relations in the nature of improving the image of PT. Jakarta Transportation. This research method uses descriptive qualitative methods. This research uses the concept of Scott M Cutlip and Allen Center regarding the function of Public Relations. Data collection techniques use in-depth interviews, observation and documentation techniques. The results of this study show that the Public Relations Function at PT. Jakarta transportation is very good to know the improvement of service felt by customers